(untitled) (Biological Sciences - PJSIR, 2009)
In the investigations on peanut hull as a low cost locally available biosorbent for the potential to remove reactive, acid and disperse dyes from aqueous solutions, the acid treated peanut hulls exhibited maximum adsorption efficiency as biosorbent.